The crow - Shaheen, safdar (Children publications; Karachi, 2008)
"The Crow by Quran Stories for Children" is a child-friendly retelling of the Quranic story of the crow, imparting moral lessons about responsibility, the value of life, and the wisdom imparted by nature.